ETIOLOGY AND FEATURES OF THE CLINICAL MANIFESTATION OF ODONTOGENIC PHLEGMON - Abdullayev, Sh.Y.; Bobokhodjaev, A.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The review article presents information on the achievements in the field of research of the features of the etiology and clinical manifestation of odontogenic phlegmon. It has been shown that in recent years there has been a clear trend towards an increase in the virulent properties of microflora, and the emergence of antibiotic-resistant and even antibiotic-dependent strains. This is especially true of the causative agents of nosocomial infection, the pathogenetic role of which has recently increased significantly. Antibiotics, being powerful selective factors, contribute to the accumulation in the population of resistant forms of bacteria and the formation of drug-resistant species with altered pathogenic and other properties. In addition, the massive, uncontrolled use of modern antibacterial and anti-inflammatory drugs leads to a violation of the natural biological balance in the microbiocenosis and the dominance of opportunistic microorganisms - the main causative agents of purulent and purulent-necrotic inflammatory processes of the soft tissues of the face and neck. The interest of researchers in the biological properties of microorganisms, namely in the persistence factors that determine the course of the infectious process, remains unclear. The relationship between the persistent properties of bacterial pathogens and the dynamics of the species composition of the causative agents of odontogenic phlegmon remains unclear; the state of the persistence factors of microorganisms that form bacterial associations in the foci of surgical infection has not been studied. There is a need to improve microbiological diagnostics for atypically current purulent-inflammatory diseases, to establish the main pathogens, and to determine the factors of persistence of microorganisms, which will allow a finding of new solutions, both for the diagnosis and for predicting the course of odontogenic inflammatory diseases.